Austenite reversion kinetics and stability during tempering of a Ti-stabilized supermartensitic stainless steel: Correlative in situ synchrotron x-ray diffraction and dilatometry. (1st October 2017) - Escobar, J.D.; Faria, G.A.; Wu, L.; Oliveira, J.P.; Mei, P.R.; Ramirez, A.J.
Abstract: Correlative physical simulation, synchrotron x-ray diffraction and laser dilatometry were used to characterize the surface and volumetric austenite reversion kinetics and stability in a Ti-stabilized supermartensitic stainless steel. A fast heating rate of 500 °C s −1 was used to minimize any martensite to austenite reversion related to the heating stage. This allowed the characterization of the austenite reversion kinetics and its corresponding thermal stability on cooling for tempering temperatures between 600 and 700 °C. In all cases, a soaking time of 9000 s and a cooling rate of 5 °C s −1 were used. The isothermal transformation was divided in two regimes: At and above 625 °C, the kinetics of the transformation was faster and the austenite equilibrium volume fraction was reached. Below 625 °C, the transformation was slower and incomplete. The reverted austenite was stable during cooling after tempering at and below 610 °C, partially stable for temperatures between 625 and 650 °C, and unstable for temperatures between 670 and 700 °C. The austenite Ni content should be higher than 8 wt % in order to effectively stabilize austenite at room temperature. Correlated bulk (dilatometry) and surface (diffraction) analyses showed very good agreement during the isothermal stage. However, martensitic transformation at the sample surface was evidenced at higher temperatures related to the bulk due to the free surface effect. A reversion TTT diagram and the austenite stability curve were constructed from the in situ x-ray diffraction data, providing tools for microstructural and performance optimization of this material. Graphical abstract: Image 1